2020
DOI: 10.1177/1756286420969462
|View full text |Cite
|
Sign up to set email alerts
|

Possible coexistence of MOG-IgG-associated disease and anti-Caspr2 antibody-associated autoimmune encephalitis: a first case report

Abstract: Myelin oligodendrocyte glycoprotein antibody-associated disease has been proposed as a separate inflammatory demyelinating disease of the central nervous system (CNS) since the discovery of pathogenic antibodies against myelin oligodendrocyte glycoprotein (MOG-IgG). Antibodies targeting contactin-associated protein-like 2 (Caspr2), a component of voltage-gated potassium channel (VGKC) complex, have been documented to be associated with a novel autoimmune synaptic encephalitis with a low incidence. Herein, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The results showed that the antibody titers of serum and CSF were 1:1 to 1:100. A previous study revealed that the titers and types of antibodies also changed during the course of disease progression (28)(29)(30), which can be used for disease assessment and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the antibody titers of serum and CSF were 1:1 to 1:100. A previous study revealed that the titers and types of antibodies also changed during the course of disease progression (28)(29)(30), which can be used for disease assessment and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-three relevant studies were identified after title and abstract screening. After reading the full texts and reviewing the references of the retrieved articles, 35 studies were finally included in the qualitative synthesis, of which 14 were retrospective studies [ 11 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and 21 were case reports [ 12 , 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. A total of 113 patients (46 males and 67 females) were reported to show the coexistence of MOG-IgG and neuronal or glial antibodies in these 35 studies.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the spectrum of MOGAD has been expanded due to the detection of MOG-IgG coexisting with other neuronal or glial antibodies, especially in patients with atypical clinical symptoms and/or neuroradiological features [ 11 ]. Our group recently reported two patients with atypical MOGAD in whom MOG-IgG coexisted with glial fibrillary acidic protein (GFAP)-IgG [ 12 ] and contact protein-associated 2 (CASPR2)-IgG [ 13 ], respectively. An increasing number of studies have also demonstrated the coexistence of MOG-IgG with other antibodies, such as N-Methyl-D-Aspartate Receptor (NMDAR)-IgG [ 14 ] and AQP4-IgG [ 15 , 16 ], which has drawn extensive attention and generated discussion.…”
Section: Introductionmentioning
confidence: 99%
“… 68 , 75 Given the overall rarity of double positive cases based on the results of the larger studies, and considering the superior specificity of the AQP4-IgG test compared to the MOG-IgG test, and that a reliable cell-based-assay (CBA) for detecting MOG-IgG has been available just recently (2017), there is a high possibility that most of the double positive cases may likely be AQP4-IgG + NMOSD with false positive MOG-IgG test results, especially in reports made before this time with using enzyme-linked immunosorbent assay (ELISA). 68 , 75 …”
Section: Discussionmentioning
confidence: 99%